Machiavelli in contemporary media - Polegato, Andrea; Benincasa, Fabio (Springer International Publishing AG, 2021)
Intro -- Foreword: Machiavelli in Hell -- Murder -- Diabolical Atheism -- References -- Acknowledgments -- Contents -- Notes on Contributors -- List of Figures -- Chapter 1: Introduction -- Machiavelli's Masks -- Machiavelli as a Pop Object -- Machiavelli in Contemporary Media -- References -- Chapter 2: The Iconography of Power: From Machiavelli's Portraits to the Pop Art -- Machiavelli: Two Portraits from Memory between Praise and Symbolism -- The Prince and the Courtier as Political Figures -- Napoleonic Propaganda -- From the Totalitarian Prince to Pop Art -- References -- Chapter 3: "Unarmed Prophets Have Always Been Destroyed, Whereas Armed Prophets Have Succeeded:" Machiavelli's Portrayal in the Assassin's Creed Series -- Cultural Studies and Assassin's Creed -- Machiavelli in Assassin's Creed: Facts Meet Fiction -- Machiavelli in AC: Interactivity, Convergence and Narratives -- Machiavelli as a Video Game Character: Relevance and Reception -- Using Assassin's Creed as a Learning Device? -- Video Game-Based Learning and Machiavelli -- The Assassin's Creed Series as a Contemporary Cultural Artifact -- Is Video Game-Based Learning Effective? -- References -- Chapter 4: Why Write a Graphic Novel about Machiavelli? -- Machiavelli's Style -- Vita di Niccolò Machiavelli fiorentino -- The Two Renaissances of the Florentine Niccolò Machiavelli -- References -- Chapter 5: Ghosts of Machiavelli in Italian Political Cinema -- Machiavelli: A Burdensome Father -- Men of Action and Unarmed Prophets -- Post-Neorealist Political Cinema: Dostoevsky Vs. Marx -- Politics and Evil in the New Millennium -- A New Perspective on Power and Society -- References -- Chapter 6: Invisible Ends Justify Secret Means: Homeland, Machiavelli, and the Least of All Possible Evils -- The Means and the End -- Reason of State and Personal Reasons -- Collateral Damages.